FAKTOR-FAKTOR YANG MEMENGARUHI MINAT PETANI DALAM BERUSAHATANI LADA DI DESA AIR GEGAS KABUPATEN BANGKA SELATAN - Atmaja, Eddy Jajang Jaya; Sari, Indah; Muntoro, Muntoro (Journal of Integrated Agribusiness, 2024)
This study aims to describe the characteristics of farmers based on factors that influence farmers' interest in pepper farming and analyze what factors influence farmers' interest in pepper farming in Air Gegas Village, South Bangka Regency. The time and place of this research will be carried out in June 2023 on pepper farmers in Air Gegas Village, South Bangka Regency. The data collection used are observation, interview, and questionnaire methods. The data analysis method uses quantitative descriptive and logistic binary regression with SPSS tools. The results showed that Factors that influence farmers' interest in pepper farming in Air Gegas Village, South Bangka Regency are the age of farmers, pepper farming experience, pepper selling prices, capital availability, agricultural assistance, and farmers' perceptions of pest and disease attacks, while those that do not affect are farmer education.